Inclusive Dialogues: Lessons for a More Accessible University - del Valle, Marta P. (Revista del Hospital Italiano de Buenos Aires, 2026)
Drawing on the experience of the Inclusive Dialogue Spaces, this editorial reflects on inclusion as a challenge that goes beyond individual support measures. It proposes viewing accessibility as an opportunity for institutional learning and highlights the need to strengthen faculty competencies in order to build more inclusive universities.
Keywords: Inclusive education; accessibility; higher education; educational quality; faculty development